Does partial blockade of dopamine D2 receptors with Amisulpride cause anhedonia? An experimental study in healthy volunteers. (February 2023) - Berg, Max; Riehle, Marcel; Rief, Winfried; Lincoln, Tania
Abstract: Background: Anhedonia is a frequent cause of functional im p airment in psychosis. Although it is plausible that medication-induced D2 receptor blockade could diminish hedonic responding, there is little experimental research testing this hypothesis in humans. Methods: To inspect possible effects of partial D2 blockade on hedonic experiences, we administered 300 mg of Amisulpride or placebo to 85 participants in a randomized, double-blind, placebo-controlled trial. Participants were then subjected to an emotional evocation task utilizing standardized pictorial pleasant, neutral, and unpleasant stimuli. Results: We observed lower positivity ratings in the Amisulpride group compared to placebo across all stimulus categories ( p  = .026, f  = 0.25) and no group differences in negativity or arousal ratings. The Amisulpride group also showed lower electrodermal responses across all stimulus categories compared to placebo ( p = . 017, f  = 0.27). The electrodermal response was especially diminished for pleasant stimuli. Conclusion: We interpret our findings as evidence that D2 blockade via Amisulpride can reduce at-the-moment hedonic responsivity in healthy volunteers. If these results can be confirmed in drug-naïve clinical samples, this would indicate that antipsychotic medication contributes to clinical anhedonia, probably via antagonistic effects at the dopamine D2 receptor. Highlights: Amisulpride reduces hedonic responses towards visual stimuli in healthy volunteers. These reductions are accompanied by diminished skin conductance responses. The reductions may be a consequence of D2R antagonism of Amisulpride. A medium dose of 300 mg (compared to placebo) was sufficient to induce these effects.